Analysis of strain correction procedures for single fiber tensile testing. (April 2023) - Engelbrecht-Wiggans, Amy E.; Forster, Amanda L.
Abstract: Accurate strain measurement for single fibers is critical for many engineering applications. Typically, the crosshead displacement is used to calculate strain when performing mechanical testing, however there are complicating factors: slack in the specimen or slipping/seating in the grips, other grip effects, and load frame compliance. These are addressed in various testing standards for single fibers, such as ASTM Standards D3822, "Standard Test Method for Tensile Properties of Single Textile Fibers" and C1557, "Standard Test Method for Tensile Strength and Young's Modulus of Fibers". In this work, an analysis of single fiber test data has been performed to examine both ASTM Standard D3822 and ASTM Standard C1557 to evaluate the utility of these standards for strain correction. Furthermore, a Monte-Carlo simulation has been performed to investigate the sensitivity of the results to various single fiber parameters. These analyses indicate that while the standards provide valuable instructions for performing tensile testing, the suggested methods for strain correction do not aid in accurately determining engineering strain.